A 3D flower-like WC with large capacitance as efficient co-catalyst in photocatalytic H2 evolution. (16th November 2021) - Dang, Yuying; Feng, Li; Hu, Wenfeng; Wang, Wei; Zhang, Qiaohong; Ma, Baojun
Abstract: Non-noble metal co-catalysts can promote photo-excited charge separation of semiconductor and act as active sites for proton catalytic H2 evolution. However, how to judge which function non-noble metal co-catalyst has is not clear. Here, we reported a 3D flower-like WC (WC–F) which shows outstanding activity (24502 μmol/h/g) on CdS in photocatalytic H2 evolution. WC–F has the largest specific capacitance (12.07 F/g), which contributes to the largest electron storage capability. The integration of noble metal Pd and WC tests demonstrated WC–F has the largest proton reduction catalysis ability. Significantly, composite co-catalyst Pd/WC–F on CdS shows slightly higher (1.16 times) activity than WC–F/CdS, which means most of photoexcited electrons on WC–F have been consumed and reaction with protons to produce hydrogen. Thus, two judgement methods for both charges storage and protons catalysis were put forward. Graphical abstract: H2 evolution mechanism of Lotus-White lotus root-Green lotus leaf. Image 1 Highlights: 3D flower-like WC–F loaded on CdS shows the best photocatalytic activity. Pd is the most excellent co-catalyst among noble metals. (Pd/WC–F)/CdS hardly enhances activity of WC–F/CdS, demonstrating WC-F has strong catalytic ability. A criteria is proposed to judge whether a non-noble metal co-catalyst has strong catalytic ability.